Dual-function surface hydrogen bonds enable robust O2 activation for deep photocatalytic toluene oxidation. Issue 1 (14th November 2020) - Li, Hao; Jiang, Fuze; Drdova, Sarka; Shang, Huan; Zhang, Lizhi; Wang, Jing
Abstract : Extensive hydrogen-bonds between the hydroxyl-rich BiOCl surface and phosphoric acid significantly facilitate oxygen vacancy formation, O2 activation, and deep toluene oxidation. Abstract : Solar-driven molecular oxygen activation by semiconductor photocatalysts is a prototypical reaction manifesting complex interactions among photons, charge carriers, and reactants. In this study, we demonstrate that energetic O2 activation towards volatile organic compound control can be realized via constructing a sophisticated surface hydrogen bond (HB) network having a dual-function. The extensive HBs established between the hydroxyl-rich BiOCl surface and phosphoric acid are first shown to significantly weaken surface Bi–O bonds, enabling facile oxygen vacancy (OV) generation. OVs, which act as reliable electron capture and static O2 activation centers, reinforce the interaction between photons and excitons for rapid charge carrier separation. Moreover, dynamic O2 activation with sluggish kinetics can be surmounted by another type of HB localized between hydroxyl groups of phosphoric acid and OV-adsorbed O2 . These unique localized HBs facilitate interfacial electron transfer from BiOCl to O2, displaying a unique energy coupling route between charge carriers and reactants. For simulated indoor toluene oxidation, the substantially boosted O2 activation is shown to accelerate the kinetic processes associated with the primary oxidation of toluene into benzaldehyde and benzoic acid, as well as aromatic ring opening towards deep oxidation. Undesirable intermediate accumulation and catalyst deactivation are thus avoided. The present work highlights the pivotal roles of HBs in robust photocatalytic O2 activation. It will provide novel insights into the design of high-performance catalysts for efficient and safe control of indoor volatile organic compounds.